Economic implications of the transition from face-to-face to virtual modality in university students (Revista de Investigaciones Universidad del Quindío, 2022)
Due to the need and urgency brought about by the COVID-19 health crisis, governments closed the doors of educational institutions as a measure to mitigate the effects of the pandemic, thus affecting 94% of students worldwide (UNESCO, 2020). Therefore, according to the WHO, teachers, administrators, and students should continue to acquire knowledge and skills despite the pandemic, but now virtually to protect themselves from the school risks they face, so that they can acquire knowledge safely and effectively. The present study aims to know the economic position of accounting students in the Academic Division of Economic-Administrative Sciences during the transition from face-to-face to virtual education in the face of the pandemic in the period from June to October 2020, with the purpose that the teacher can adopt good practices to ensure the good school performance of students. The study is descriptive, cross-sectional, retrospective and analytical. Surveys were applied to university students, 47% of the population were female and 53% were male. The results show that 98% of the students had access to technology, although only 66% were able to use it without problems, such as lack of internet, poor signal, electricity, among others. It is concluded that among the economic implications that the epidemic imposes on home conditions is that many students have limited access to wifi and must take their lessons through their mobile devices or cell phones using data consumption, in some cases, the service does not reach their homes, which limits good communication. That is why for teachers and educational institutions it is a great challenge, since they must use all the ingenuity and creativity to have learning methodologies that enhance the quality of students.
Keywords: Economic impact; family wealth; virtual migration; university students